Characteristics of plantar loads in maximum forward lunge tasks in badminton - Hu, X.; Li, J. X.; Hong, Y.; Wang, L. (PLOS ONE, 2015)
Badminton players often perform powerful and long-distance lunges during such competitive matches. The objective of this study is to compare the plantar loads of three one-step maximum forward lunges in badminton. Methods: Fifteen right-handed male badminton players participated in the study. Each participant performed five successful maximum lunges at three directions. For each direction, the participant wore three different shoe brands. Plantar loading, including peak pressure, maximum force, and contact area, was measured by using an insole pressure measurement system. Two-way ANOVA with repeated measures was employed to determine the effects of the different lunge directions and different shoes, as well as the interaction of these two variables, on the measurements. Results: The maximum force (MF) on the lateral midfoot was lower when performing left-forward lunges than when performing front-forward lunges (p = 0.006, 95% CI = -2.88 to -0.04%BW). The MF and peak pressures (PP) on the great toe region were lower for the front-forward lunge than for the right-forward lunge (MF, p = 0.047, 95% CI = -3.62 to -0.02%BW; PP, p = 0.048, 95% CI = -37.63 to -0.16 KPa) and left-forward lunge (MF, p = 0.015, 95% CI = -4.39 to -0.38%BW; PP, p = 0.008, 95% CI = -47.76 to -5.91 KPa). Conclusions: These findings indicate that compared with the front-forward lunge, left and right maximum forward lunges induce greater plantar loads on the great toe region of the dominant leg of badminton players. The differences in the plantar loads of the different lunge directions may be potential risks for injuries to the lower extremities of badminton players.